Management of Certain Respiratory Disorders through Ayurveda: A Systematic Review of Clinical Studies Published in Ayurveda Journal - Sreedharan, Anju; Suryawanshi, Nilesh; Bhapkar, Vedvati (Current Traditional Medicine, 2022)
Background: Respiratory diseases like Asthma, Tuberculosis, and COPD (Chronic Obstructive Pulmonary Diseases) in the developing world are a major health burden in terms of morbidity and mortality in both adults and children. A number of studies on treating respiratory disorders using Ayurveda formulations and theirmanagement have been found in Ayurveda Journals with promising results, but an evidence-based systematic review of them is not available. Objective: The objective of this study is to conduct a systematic review on the management of certain respiratory disorders through Ayurveda. Methods: To conduct this study, Ayurveda research articles were obtained from PubMed and Google Scholar. Total 51 clinical studies were yielded, which underwent further screening process to achieve the quality of inclusion criteria. Results: 24 articles were selected from six different publications for the review. In general, the quality of few selected articles was low. Of the 24 articles identified, 3 studies (n = 24) exclusively focused on Shodhana Karma (Vamana Virechana), 3 studies (n = 24) focused on the concept of Shodhana and Shamana Chikitsa, 4 studies (n = 24) focused on Ayurvedic formulations as adjuvants, 1 study (n = 24) focused on Shamana Chikitsa along with Pranayama, 13 studies (n = 24) focused only on Shamana Chikitsa. All the above treatment modalities showed significant results on major symptoms of respiratory disorders. Conclusion: This systematic review on different types of Ayurvedic management for treating respiratory disorders proves to be beneficial to understand the importance of Virechana Karma in Tamaka Swasa, the effectiveness of Shamana Chikitsa after Shodhana Karma in Pratishaya and Tamaka Swasa. This review also sheds light on the importance of Pranayama along with Shamana Chikitsa, efficacy of Ayurvedic formulations as adjuvant along with allopathic treatments and potency of different Ayurvedic dosage forms for treating certain respiratory disorders.
Keywords: clinical studies